Marketing the Nissan Micra and Tata Nano using social media - Tybout, Alice M.; Fahey, Natalie ([London] : SAGE, 2016)
The case explores the similarities and differences between social media campaigns launched by Nissan and by Tata Motors to stimulate sales for models of their cars in India. The Nissan campaign allowed consumers to compete to star with Ranbir Kapoor, a Bollywood star and spokesman for the Nissan Micra, in a short film featuring the Micra as the hero. The Tata campaign launched India's first social streaming show, in which select teams of consumers participated in an Amazing Race-style road trip competition in different regions of the country. Both campaigns made extensive use of Facebook. Students are tasked with evaluating the two campaigns in terms of their fit with the communication objectives of each company and their effectiveness on a variety of metrics.
Originally Published in: Tybout, A. M., & Fahey, N. (2012). Marketing the Nissan Micra and Tata Nano Using Social Media (case revised 17/01/2013). 5-412-752. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Nissan Jidosha Kabushiki Kaisha; Tata Motors; Marketing -- Case studies; Social media -- Case studies; Automobile industry and trade -- India -- Case studies